2018
DOI: 10.1158/2326-6066.cir-17-0659
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Pancreatic Atrophy Induced by Immune-Checkpoint Inhibitors: A Case–Control Study

Abstract: Immune-checkpoint inhibitor (ICI)-related diarrhea is attributed to inflammatory colitis, with no other drug-related differential diagnosis. Here, we investigated the occurrence of pancreatic atrophy (PA) in ICI-treated cancer patients and its correlation to exocrine pancreatic insufficiency (EPI). Metastatic melanoma, non-small cell lung carcinoma, and head and neck squamous cell carcinoma patients (n ¼ 403) treated with anti-PD-1 (n ¼ 356) or anti-CTLA-4 (n ¼ 47) were divided into a case group (radiologic ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Multiple studies have shown that morphometric and radiomic metrics derived from morphologically normal pancreas can be biomarkers in diabetes, obesity, nonalcoholic fatty liver and pancreas disease, metabolic syndrome, and in patients undergoing immunotherapy for nonpancreatic malignancies. [1][2][3]8,[12][13][14] However, the quantitative changes in these metrics are beyond the perceptive abilities of the naked eye. Therefore, the pancreas appears morphologically normal on visual inspection in these subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies have shown that morphometric and radiomic metrics derived from morphologically normal pancreas can be biomarkers in diabetes, obesity, nonalcoholic fatty liver and pancreas disease, metabolic syndrome, and in patients undergoing immunotherapy for nonpancreatic malignancies. [1][2][3]8,[12][13][14] However, the quantitative changes in these metrics are beyond the perceptive abilities of the naked eye. Therefore, the pancreas appears morphologically normal on visual inspection in these subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Our decision to develop a model for segmentation of morphologically normal pancreas was based on anticipated clinical applications. Multiple studies have shown that morphometric and radiomic metrics derived from morphologically normal pancreas can be biomarkers in diabetes, obesity, nonalcoholic fatty liver and pancreas disease, metabolic syndrome, and in patients undergoing immunotherapy for nonpancreatic malignancies 1–3,8,12–14 . However, the quantitative changes in these metrics are beyond the perceptive abilities of the naked eye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early endoscopy was associated with faster resolution of enterocolitis symptoms and shorter duration of glucocorticoid use in a retrospective analysis [20]. Endoscopy may be useful in identifying rare patients with CPI associated gastrointestinal symptoms that are not related to mucosal inflammation [21, 22], as well as patients with colonic ulceration who are more likely to fail initial management with glucocorticoids [10, 11]. Although mucosal changes are common in patients with CPI enterocolitis, a subset of patients have normal-appearing mucosa on endoscopy and lymphocyte-predominant inflammation [6, 23].…”
Section: Introductionmentioning
confidence: 99%
“…In our case, antibodies were absent. Several studies have reported mild elevations of serum amylase and serum lipase, without features of pancreatitis on imaging, although pancreatic atrophy may be seen [5,6].…”
mentioning
confidence: 99%